Different beliefs about pain perception in the vegetative and minimally conscious states: a European survey of medical and paramedical professionals - Demertzi, A; Schnakers, C; Ledoux, D; Chatelle, C; Bruno, M-A; Vanhaudenhuyse, A; Boly, M; Moonen, G; Laureys, S (Progress in brain research, 2009)
Pain management in severely brain-damaged patients constitutes a clinical and ethical stake. At the bedside, assessing the presence of pain and suffering is challenging due to both patients' physical condition and inherent limitations of clinical assessment. Neuroimaging studies support the existence of distinct cerebral responses to noxious stimulation in brain death, vegetative state, and minimally conscious state. We here provide results from a European survey on 2059 medical and paramedical professionals' beliefs on possible pain perception in patients with disorders of consciousness. To the question "Do you think that patients in a vegetative state can feel pain?," 68% of the interviewed paramedical caregivers (n=538) and 56% of medical doctors (n=1166) answered "yes" (no data on exact profession in 17% of total sample). Logistic regression analysis showed that paramedical professionals, religious caregivers, and older caregivers reported more often that vegetative patients may experience pain. Following professional background, religion was the highest predictor of caregivers' opinion: 64% of religious (n=1009; 850 Christians) versus 52% of nonreligious respondents (n=830) answered positively (missing data on religion in 11% of total sample). To the question "Do you think that patients in a minimally conscious state can feel pain?" nearly all interviewed caregivers answered "yes" (96% of the medical doctors and 97% of the paramedical caregivers). Women and religious caregivers reported more often that minimally conscious patients may experience pain. These results are discussed in terms of existing definitions of pain and suffering, the remaining uncertainty on the clinical assessment of pain as a subjective first-person experience and recent functional neuroimaging findings on nociceptive processing in disorders of consciousness. In our view, more research is needed to increase our understanding of residual sensation in vegetative and minimally conscious patients and to propose evidence-based medical guidelines for the management of possible pain perception and suffering in these vulnerable patient populations.